Transcriptome Dynamics in Arabidopsis Thaliana Male Germ Unit: From Mature Pollen Grain to Pollen Tube - Misra, Chandra Shekhar (2021)
"Pollen development in flowering plants initiates within anthers, where microspore mother cells undergo meiosis to form haploid microspores. The haploid microspore undergoes asymmetric division (pollen mitosis I) to form a larger vegetative cell harbouring a smaller generative cell that undergoes a second mitotic division (pollen mitosis II) to form two sperm cells."